Early Exposure of Antibiotic as A Risk Factor for Gastrointestinal Disorders: An Evidence-Based Case Report - Ezy Barnita; Lukito Ongko; Muzal Kadim (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Background: Incidence rate of pediatric onset inflammatory bowel disease (IBD) has been increasing worldwide particularly in the rapidly growing countries. It has been hypothesized that environmental factors such as method of delivery, rural or urban living environment and the use of antibiotics, may play significant roles. Antibiotics are known to alter gut microbiome and henceforth may be the rational mechanism in the development of gastrointestinal autoimmune diseases. Methods: Literature search was performed on 3 international databases (PubMed, PubMed PICO and Google Scholar) by using relevant keywords based on clinical question. Results: Two systematic reviews were included in this study. Both studies reported strong evidence regarding the increase risk of occurrence for inflammatory bowel disease and celiac disease after exposure of antibiotics particularly in young age Discussion: At young age, the immune system and gut microbiota is considered to be unstable and prone to disruption particularly by exposure of antibiotics. Antibiotics is known to weaken mucosal barrier of the gut which facilitates translocation of commensal bacteria. Translocation process together with the imbalance ratio of T-helper 1 and T-helper 2 may be the pathogenesis behind the development of chronic gastrointestinal diseases. Conclusion: There is strong evidence that early life exposure to antibiotic is associated with the development of IBD and Celiac disease in childhood. Therefore, it is critical for all healthcare workers to adhere to strict guidelines regarding the rationality on when to prescribe antibiotics particularly in children of young age.